Bad medicine : catching New York's deadliest pill pusher - Bismuth, Charlotte (One Signal Publishers/Atria Books, 2021)
"The shocking story of New York's most infamous pill-pushing doctor, written by the prosecutor who brought him down in a landmark and precedent-setting case in the fight against opioid addiction" --